Pengaruh Influencer Marketing dan Content Marketing terhadap Purchase Decision dengan Brand Awareness dan Perceived Value sebagai Variabel Mediasi - Maharani, Yunia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to explore the influence of Influencer Marketing and Content Marketing on Purchase Decision, with Brand Awareness and Perceived Value as mediating variables. A quantitative approach was employed through a survey using a Likert-scale questionnaire (1-10), distributed to 225 TikTok users selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. The results show that Influencer Marketing and Content Marketing have a positive and significant impact on Brand Awareness and Perceived Value. Additionally, Brand Awareness and Perceived Value also significantly affect Purchase Decision. These findings highlight that Influencer Marketing and Content Marketing strategies not only enhance brand awareness and consumer perceived value but also contribute to an increase in purchase decisions.